2017
DOI: 10.1038/ctg.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Some Remaining Challenges in Hereditary Gastrointestinal Cancer Panel Testing

Abstract: Colorectal cancer affects 1 in 20 men and women in their lifetime. About 30% of these cases have been shown to be familial while only about 5% are associated with a highly penetrant hereditary colon cancer syndrome. In many familial cases, however, no mutation in the commonly implicated CRC genes is found. With the development of next-generation sequencing, testing laboratories are now able to offer hereditary gastrointestinal panel testing, which allows for the simultaneous sequencing of a much broader set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…VUS represents an important challenge for the clinician and could become a significant source of anxiety and distress for patients, although the official recommendation in the setting of a VUS is to manage the patient on the basis of the personal and family history. 8,11,12,23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VUS represents an important challenge for the clinician and could become a significant source of anxiety and distress for patients, although the official recommendation in the setting of a VUS is to manage the patient on the basis of the personal and family history. 8,11,12,23…”
Section: Discussionmentioning
confidence: 99%
“…57 Although multigene testing has been proven to be an efficient approach for comprehensive, cost-effective, and time-saving evaluation of multiple genes, 810 its introduction into routine practice raises many concerns about its impact on result interpretation as well as patient counseling and management. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Germline mutations in GI cancer susceptibility genes, including MLH1, MSH2, MSH6, APC, CDKN2A, CDH1 and PALB2 are reported. [ 36 - 38 ]…”
Section: Major Risk Factors Of Gi Cancersmentioning
confidence: 99%
“…Germline mutations in GI cancer susceptibility genes, including MLH1, MSH2, MSH6, APC, CDKN2A, CDH1 and PALB2 are reported. [36][37][38] Other GI diseases Several diseases of the GI tract, if untreated, may develop into cancer. Gastritis, a stomach inflammation, if chronically persists, can cause gastric cancer.…”
Section: Hereditary Factorsmentioning
confidence: 99%
“…According to Ferlay et al, (2019) estimations showed that in 2018, approximately 18.1 million new cancer cases and 9.6 million cancer deaths were recorded in the world. It is expected that new cases will increase with the highest percentage and burden occurring in developing countries by 2030 (Maga et al, 2017). While a diagnosis of cancer was once considered a death sentence, in recent years, cancer survival statistics have dramatically improved with more than 50% of newly diagnosed patients surviving beyond 5 years after diagnosis (Jalai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%